Intussusception Associated with Sand Accumulation in a Greater Rhea (Rhea americana) - Batista Jael Soares (Sciendo, 2021)
Pathoanatomical studies of diseases that affect wild animals are extremely important as appropriate measures can then be taken for the prevention and control of such diseases. We report here the case of death of a greater rhea (Rhea americana) by intestinal intussusception secondary to the ingestion of a large amount of sand. The animal was bred at the Center for Multiplication of Wild Animals of the Federal Rural University of the Semi-Arid. The animal died after presenting clinical signs of apathy, weakness, prostration, and inability to move, drink water, or eat. After death, the carcass was immediately sent for necropsy. During necropsy, intussusception was found involving the jejunum, ileum, and colon. The duodenum contained large amounts of coarse sand. The invaginated intestinal segments were reddish in color, with necrotic spots, and covered by a fibrinous exudate. Histopathological examination of the invaginated segments showed necrosis of the enterocytes, detachment of the intestinal epithelium, and the presence of inflammatory cells. The ingestion of a large amount of sand may have resulted in altered intestinal transit, contributing to the occurrence of intussusception, which resulted in ischemic alterations, intestinal necrosis, and consequent death of the animal.